Novel Tryptanthrin Derivatives with Selectivity as c–Jun N–Terminal Kinase (JNK) 3 Inhibitors - Schepetkin (Shchepyotkin) I. A. Igor Aleksandrovich; Karpenko O. S. Oleksandr; Kovrizhina A. R. Anastasia Ruslanovna; Kirpotina L. N. Liliya Nikolaevna; Khlebnikov A. I. Andrey Ivanovich; Chekal S. I. Stepan; Radudik A. V. Alevtina; Shybinskaya M. O. Marina; Quinn M. T. Mark (2023, 2023)
Title screen